Case Report: A case of membranous nephropathy associated with primary Sjögren’s syndrome treated with telitacicept - Chen, Juan; Zhou, Fangfang; Shen, Jian; Pang, Jun; Chu, Hanqing (Frontiers in Immunology, 2025)
Primary Sjögren’s syndrome (pSS) is an autoimmune disease that often affects the exocrine glands. However, pSS can also affect the kidneys, most commonly involving the kidney interstitium. Recent studies have demonstrated that some membranous nephropathy (MN) cases are associated with Sjögren’s syndrome. However, unified recommendations for selecting immunosuppressive agents for treating MN associated with pSS are currently lacking. In the case reported herein, a patient with MN associated with pSS experienced improvement following methylprednisolone and telitacicept treatment.